Peran Gamification dalam Meningkatkan Keterlibatan Mahasiswa pada Pembelajaran Jarak Jauh: Suatu Studi Literatur - Kinanti, Afra Diar; Nurhayati; Sani, Naufal Hajid; Wicaksono, Dirgantara (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Distance learning faces major challenges related to low levels of student engagement, which are reflected in limited participation, decreased motivation, and a weakened sense of connectedness in online learning environments. Gamification has emerged as a pedagogical approach with the potential to enhance student engagement; however, previous studies report mixed findings, largely depending on how gamification is designed and implemented. This article aims to theoretically examine the role of gamification in enhancing student engagement in distance learning through an integrative literature review. The analysis focuses on the three dimensions of student engagement; behavioral, emotional, and cognitive and relates them to the Community of Inquiry framework, which includes teaching presence, social presence, and cognitive presence. The synthesis of the literature indicates that instructionally designed gamification aligned with learning objectives can reduce students’ sense of isolation, increase learning interactivity, and strengthen the sense of progress that is often diminished in conventional online learning. In contrast, superficial gamification tends to produce limited and unsustainable motivational effects. This article argues that the effectiveness of gamification in distance learning is largely determined by the quality of pedagogical design, the fulfillment of students’ psychological needs, and its integration within the online learning ecosystem. The findings of this review are expected to provide a conceptual foundation for developing more meaningful and student-centered distance learning designs